Antioxidant effect of saponin: potential action of a soybean flavonoid on glucose tolerance and risk factors for atherosclerosis - Rodrigues, H. G.; Diniz, Y. S.; Faine, L. A.; Galhardi, C. M.; Burneiko, R. C.; Almeida, J. A.; Ribas, B. O.; Novelli, ELB (Taylor & Francis Ltd, 2005)
At the present time, much attention is being paid to antioxidant substances because many pathological conditions are associated with oxidative stress. The purpose of the present study was to discover the potency of saponin (2-phenyl-benzopyrane), a soybean flavonoid, with respect to its hypoglycaemic and hypolipidaemic action, and the association of these effects with oxidative stress. Male Wistar rats were divided into two groups (n = 6): control group and saponin-treated group (60 mg/kg) during 30 days. Saponin had no effects on glucose tolerance. Although no changes had been observed in low-density lipoprotein-cholesterol, saponin-treated animals had increased low-density lipoprotein-cholesterol/triacylglycerol ratio and decreased triacylglycerol, very low-density lipoprotein-cholesterol and total/high-density lipoprotein-cholesterol ratio than the control group. Saponin-treated rats showed lower lipid hydroperoxide than control rats, indicating decreased potential to atherosclerosis. No alterations were observed in antioxidant enzymes, superoxide dismutase and glutathione peroxidase, while lipid hydroperoxide were decreased in saponin-treated rats. In conclusion, the beneficial effects of saponin on serum lipids were related to a direct saponin antioxidant activity.